The study of noninvasive brain stimulation using molecular brain imaging: A systematic review - Sara Tremblay (NeuroImage, 2020)
Electromagnetic noninvasive brain stimulation (NIBS) techniques, such as transcranial magnetic stimulation and transcranial electrical stimulation, are widely used in research and represent emerging clinical treatment options for many brain disorders. The brain-wide neurobiological effects of electromagnetic NIBS, however, are not yet fully characterized. The combination of NIBS with molecular brain imaging is a powerful tool for the investigation of these effects. Here, we conducted a systematic review of all published studies investigating the effects of all forms of electromagnetic NIBS using molecular imaging (positron emission tomography, single photon emission computed tomography). A meta-analysis was also conducted when sufficient studies employed similar methodologies. A total of 239 articles were identified, of which 71 were included in the review. Information was extracted about the study design, NIBS parameters, imaging parameters, and observed local and remote effects caused by the stimulation. Regional cerebral blood flow and glucose metabolism were the most common outcome measures, followed by dopamine neurotransmission. While the vast majority of studies obtained remote effects of stimulation in interconnected regions, approximately half of the studies showed local effects at the stimulation site. Our meta-analysis on motor cortex stimulation also showed consistent remote effects. The literature review demonstrates that although the local effects of NIBS as captured by molecular imaging are sometimes modest, there are robust remote changes in brain activity and neurotransmitter function. Finally, we discuss the potential pitfalls and methodological issues and identify gaps in the current knowledge that could be addressed using these techniques.